Corrigendum to: A Review on Lung Cancer Diagnosis Using Data Mining Algorithms - Heydari, Farzad; Rafsanjani, Marjan (Current Medical Imaging, 2021)
Due to an oversight of the author, the principal author’s name was published incorrectly in the author list and in the Fig. (3): Shakeel et al. (2019) have been changed to Shakeel et al. (2020) and Palani and Venkata-lakshmi (2019) have been changed to Palani and Venkatalakshmi (2018) in the article entitled “A Review on Lung Cancer Diagnosis Using Data Mining Algorithms” in “Current Medical Imaging”, 2021; 17(1), [1]. The original article can be found online at https://www.eurekaselect.com/183148/article